High ANC coverage and low skilled attendance in a rural Tanzanian district: a case for implementing a birth plan intervention - Magoma, Moke (BioMed Central, 2010)
BACKGROUND: In Tanzania, more than 90% of all pregnant women attend antenatal care at least once and approximately 62% four times or more, yet less than five in ten receive skilled delivery care at available health units. We conducted a qualitative study in Ngorongoro district, Northern Tanzania, in order to gain an understanding of the health systems and socio-cultural factors underlying this divergent pattern of high use of antenatal services and low use of skilled delivery care. Specifically, the study examined beliefs and behaviors related to antenatal, labor, delivery and postnatal care among the Maasai and Watemi ethnic groups. The perspectives of health care providers and traditional birth attendants on childbirth and the factors determining where women deliver were also investigated. METHODS: Twelve key informant interviews and fifteen focus group discussions were held with Maasai and Watemi women, traditional birth attendants, health care providers, and community members. Principles of the grounded theory approach were used to elicit and assess the various perspectives of each group of participants interviewed. RESULTS: The Maasai and Watemi women's preferences for a home birth and lack of planning for delivery are reinforced by the failure of health care providers to consistently communicate the importance of skilled delivery and immediate post-partum care for all women during routine antenatal visits. Husbands typically serve as gatekeepers of women's reproductive health in the two groups - including decisions about where they will deliver- yet they are rarely encouraged to attend antenatal sessions. While husbands are encouraged to participate in programs to prevent maternal-to-child transmission of HIV, messages about the importance of skilled delivery care for all women are not given emphasis. CONCLUSIONS: Increasing coverage of skilled delivery care and achieving the full implementation of Tanzania's Focused Antenatal Care Package in Ngorongoro depends upon improved training and monitoring of health care providers, and greater family participation in antenatal care visits.